2008
DOI: 10.1051/0004-6361:200810731
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy evolution in Abell 85

Abstract: In this series of papers we explore the evolution of late-type galaxies in the rich cluster Abell 85. In this first paper we revisit the complex dynamical state of A 85 by using independent methods. First, we analyze the galaxy redshift distribution towards A 85 in the whole range 0−40 000 km s −1 , and determine the mean redshifts of the background clusters A 87 and A 89, very close in projection to A 85. Then we search for substructures in A 85 by considering the 2D galaxy distribution of its members (13 000… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
41
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 42 publications
(56 reference statements)
5
41
2
Order By: Relevance
“…Ramella et al (2007), using a different approach, detected three main structures in Abell 85. The two substructures (S 1 and S 2 ) detected by Ramella et al (2007) are close to the C2 and SB substructures reported by Bravo-Alfaro et al (2009). Figure 8 shows the substructure in Abell 85 obtained by our method.…”
Section: The Case Of Abell 85supporting
confidence: 74%
See 4 more Smart Citations
“…Ramella et al (2007), using a different approach, detected three main structures in Abell 85. The two substructures (S 1 and S 2 ) detected by Ramella et al (2007) are close to the C2 and SB substructures reported by Bravo-Alfaro et al (2009). Figure 8 shows the substructure in Abell 85 obtained by our method.…”
Section: The Case Of Abell 85supporting
confidence: 74%
“…Indeed, at the position of this group of galaxies there are no objects in our data (compare Fig. 4 from Bravo-Alfaro et al 2009;and our Fig. 7).…”
Section: The Case Of Abell 85supporting
confidence: 57%
See 3 more Smart Citations